Detection of image objects for autonomous localisation of unmanned aerial vehicles and map formation of the surrounding space - Tsviatkou, Viktor Yu.; Rabtsevich, Viyaleta V.; Jun, Ma; Zorko, Mikhail I. (Journal of the Belarusian State University. Mathematics and Informatics, 2026)
The problem of autonomous localisation of an unmanned aerial vehicle and construction of a map of its environment is considered. The low stability of keypoint detectors to changing weather and time conditions of image formation in the surrounding space is demonstrated compared to the stability of line detectors. To improve the stability of unmanned aerial vehicles localisation it is proposed to use image regions (segments) with uniform brightness as key identification objects. An algorithm for segmentation based on local minima of the brightness gradient of halftone images obtained from the original colour images of the unmanned aerial vehicle’s surrounding space has been developed. To equalise the growth rates of local minima a wave segmentation algorithm with automatic stopping is proposed. This algorithm is based on identifying new initial and additional growth points of regions using a monotonically varying threshold and taking into account the rate of change of the brightness gradient along the region growth trajectory in the stopping criterion. It is shown that the proposed algorithms provide more stable localisation of areas, when changing weather and time conditions for image formation in comparison with known algorithms for extracting lines and key points.
Keywords: simultaneous localisation and mapping; SLAM; wave segmentation of images; region growing; image object identification; point detectors; line detectors